Visual communications on a memory-embedded array processor: The Computational*RAM. - Le, Thinh Minh. (University of Ottawa (Canada), 2002)
In this thesis, image and video processing algorithms, especially the compression algorithms, are first studied in their natural formats to appreciate the needs for real-time operations and hence, parallel computing. The computational intense, memory-bound problems are next approached from two directions: algorithmic and architectural. Algorithmic approach tends to systematically analyze the flow independence and data independence of a program, while architectural approach tends to gain speed-up by resource multiplicity and time sharing. The majority of image and video processing algorithms are inherently data-parallel in nature. The vectorization of these algorithms requires consistent practices, and new challenge in parallel programming seems endless. The data-parallel nature of image/video processing algorithms map well onto the Single-Instruction stream, Multiple-Data stream (SIMD) of an increasingly popular Memory-Embedded Array Processor classified as the Intelligent RAMS, specifically, the Computational*RAM (C*RAM). C*RAM is a SIMD-memory hybrid where the processing elements are pitch-matched to memory columns of a conventional computer RAM at the sense-amplifiers to take advantage of the inherently high memory bandwidth, and the emulation of the massively parallel processors. Throughout the thesis, speed-ups from 1 to 3 orders of magnitude are obtained. Memory-bound algorithms such as Motion Estimation, and Mean-Absolute-Error for Nearest Neighbor Distortion Computation are among the most efficient implementations. At its best, this thesis will, definitely, put forward the promising research direction which involves fast and efficient in-memory parallel computing for visual communications.
Keywords: Engineering, Electronics and Electrical.